Effects of fatalism perception and attitudes towards complementary and alternative medicine on medication adherence in patients with epilepsy - Ozer, Zulfunaz; Turan, Gulcan Bahcecioglu; Karaman, Seda (Elsevier Science Inc, 2023)
Introduction: The present study was conducted to ascertain fatalism perceptions, attitudes towards complementary and alternative medicine, and medication adherence in patients with epilepsy, as well as to examine the effects of patients' fatalism perceptions and attitudes towards complementary and alternative medicine on their medication adherence. Method: This descriptive and cross-sectional study was conducted with 150 people with epilepsy admitted to the Firat University Hospital, Neurology Outpatient Clinic in Elazig, in the eastern region of Turkey. The data were collected through face-to-face interviews using the Patient Information Form, Fatalism Scale (FS), Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ), and the Eight-Item Morisky Medication Adherence Scale (MMAS-8). Results: Of the participants, 45.3% had 5 or more seizures during the past year, 30% had simple partial seizures, 26.7% also had another chronic disease, 79.8% were receiving polytherapy, 86% used their medication regularly, 65.3% had been hospitalized during the past year, and 82% used complementary medicine both for the treatment of epilepsy and during seizures. For the FS and its subscale, the mean scores of the participants were found to be 3.39 & PLUSMN;0.71 for the overall scale, 3.26 & PLUSMN;0.71 for predetermination, 3.33 & PLUSMN;0.97 for luck, and 3.59 & PLUSMN;0.89 for pessimism. The mean scores for the HCAMQ and its subscale were 32.05 & PLUSMN;9.94 for the overall questionnaire, 12.99 & PLUSMN;6.01 for holistic medicine, and 19.07 & PLUSMN;4.75 for complementary and alternative medicine. The MMAS-8 mean score was 2.14 & PLUSMN;2.04. The FS variable was found to have a negative and significant effect on MMAS-8 scores. Conclusion: Patients with epilepsy had a high level of fatalistic perception, positive attitudes toward complementary and alternative medicine, and a low level of treatment adherence. It was found that patients' treatment adherence increased as their fatalistic perceptions decreased. It can be said that the use of CAM in patients with epilepsy may be affected by fatalism.
Keywords: Complementary and Alternative Medicine; Epilepsy; Fatalism; Treatment Adherence; Patient